Continuous Sciatic Popliteal Block as Postoperative Pain Management in Patient with Closed Fracture Right Ankle Undergo ORIF PS Surgery - Santo, Budi; Tjokorda Gde Agung Senapathi (HM Publisher, 2023)
Introduction: Currently, foot and ankle surgeries are on the rise, and a significant challenge in these cases is the intense post-operative pain that arises from early patient mobilization. Continuous popliteal sciatic block have emerged as a solution, effectively alleviating pain from the intra-operative to post-operative stages for patients undergoing foot and ankle surgery. According to a study conducted by Ding and colleagues, continuous blocks have proven to be more effective than a single injection in providing pain relief. Case presentation: A 24-year-old woman diagnosed with a closed fracture of her right ankle is scheduled for open reduction internal fixation (ORIF) with a plate and screws for her right ankle. The patient has an American Society of Anesthesiologists (ASA) physical status of III and is dealing with grade II obesity. A continuous popliteal sciatic block was performed on the patient under ultrasound guidance, with the catheter tip placed outside the perineural area. Postoperatively, the patient received pain management through a regimen of 0.1% bupivacaine, 20 ml volume, administered every 4 hours. Remarkably, the patient experienced minimal pain until the 2nd day after surgery and was discharged home. Conclusion: The continuous popliteal sciatic block is a regional anesthetic method that offers potent pain relief for patients undergoing foot and ankle surgery. Extensive evidence supports its effectiveness and safety during administration, making it a reliable choice for pain management in these procedures.